Examining the role of foreign assistance in security sector reforms : the Indonesian case - Lachica, Eduardo (2009)
Indonesian and the donor community are agreed that security sector reforms are needed to restore investor confidence and sustain the pace of economic recovery. However, donor-assisted programmes have had only a limited success so far and the army's post-Suharto reforms appeared to have ground to a halt. This paper offers some suggestions on how to restore the momentum for reform in the light of donor limitations, the military's historical circumstances and the current mood of intense nationalism. Donors should initiate a quiet track II (non-official) dialogue with the military, the police, the civilian authorities and civil society to scope out a doable programme of cooperation. The issue of civilian supremacy should be dealt with pragmatically, allowing for a process of negotiation to find an effective working relationship between civilian and military authorities. The dialogue sould frame the reform process as a burden for the entire society, reminding civilian leaders that they too have responsibility to improve their performance and demonstrate their ability to oversee military affairs capably and fairly. Since U.S. assistance to the Indonesian military is likely to remain constrained, the paper proposed a "military donors club" that can expand the donor base and work informally with the World Bank-led Consultative Group on Indonesia. the dialogue should deal creatively and patiently with two of the most vexing issues relating to the army - restructuring its network of territorial commands and phasing out its controversial tradition of self-financing. This could be difficult learning process for both sides of the civilian-military divide that could last a decade or more.